Occurrence of extended- spectrum β-lactamase harboring K. pneumoniae in various sources: a one health perspective - Yasmeen, Nafeesa; Aslam, Bilal; Fang, Liang-xing; Baloch, Zulqarnain; Liu, Yahong (Frontiers in Cellular and Infection Microbiology, 2023)
This study was designed to investigate the occurrence and dissemination of extended-spectrum β-Lactamase (ESBL) harboring K. pneumoniae in various ecological niches under one health approach. A total of 793 samples were collected from animals, humans, and the environment. The findings of the study revealed the occurrence of K. pneumoniae as follows, animals (11.6%), humans (8.4%), and associated environments (7.0%) respectively. A high occurrence rate of ESBL genes was found in animals compared to human and environmental isolates. A total of 18 distinct sequence types and 12 clonal complexes of K. pneumoniae were observed. Overall, 6 STs of K. pneumoniae were identified in commercial chickens, and 3 were found in rural poultry. The majority of K. pneumoniae STs found in this study were positive for blaSHV, while the positivity of other ESBLE-encoding genes combinations was different in different STs. The high occurrence rate of ESBL-harboring K. pneumoniae found in animals as compared to other sources is alarming, and has the potential to be disseminated to the associated environment and community.